What is the impact of brain and extremity inclusion in the imaging of malignant melanoma with F-18 FDG PET/CT - Mbakaza, Olwethu Natash (My University, 2016)
Objectives: This study aimed to ascertain if there is any clinical value in including brain and extremities in the 18 F-FDG PET/CT imaging of patients with malignant melanoma. Methods: This was a retrospective study done at Charlotte Maxeke Johannesburg Academic Hospital(CMJAH), Johannesburg. All consecutive 18F-PET/CT reports for patients referred to the CMJAH department of Nuclear Medicine for an 18-F-FDG PET/CT study, spanning form 01 January 2008 to 31 December 2013, who have histologically proven malignant melanoma were included in the study. The prevalence of brain and extremity lesions of 18F-FDG PET/CT reports was documented. Hospital records were viewed to see if clinical and histological correlation was done for lesions that were likely malignant; and to also review the impact of 18F-FDG PET/CT findings on patient management. Results: One hundred and fifty nine 18F-FDG PET/CT studies in 121 patients were included for assessment. The median patient age was 54 years (ranging from 16-84 years). Eighteen patients (12%) had lesions in the brain, eight (5.33%) of which were classified as likely benign, five (3.33%) of which were classified as indeterminate. However, nine (5.7%) patients in the whole group did not have brain acquisition and were excluded from the assessment. None of the patients were likely malignant or indeterminate brain lesions underwent further investigation such as radiological correlation with MRI or a pathological correlation. Three patients had change in management as a result of finding of brain lesions on 18F-FDG PET/CT. One patient had radiotherapy of the brain with steroids, in addition to their chemotherapy regimen; another had whole brain palliative radiotherapy, in addition to their chemotherapy regimen to a different regimen. Thirty six patients (37%) had lesions in the extremities, three (8%) of the 36 were classified as likely benign, six (17%) of which were classified as likely malignant, and two (6%) of which were classified as indeterminate. The remaining twenty five (69%) had their primary tumour in the extremities. However , 61 (38%) patients in the whole group did not have acquisition of the extremities. Ninety eight patients had extremity scans. None of the patients with extremity lesions underwent further radiological and or pathological correlation, and none had a change in stage or change in clinical management Conclusion: Our study showed that although there was no change in the clinical staging resulting from the acquisition of extra brain and extremity views on 18F-FDG PET/CT, there was a change in the clinical management of those with brain lesions. There was no change in clinical management of those patients with extremity lesions. The suggested protocol is acquisition of brain views only in patients with additional metastatic lesions after the acquisition of the whole body view(base of skull to mid-thigh). The protocol, however needs validation with a more comprehensive, prospective study
A Research report submitted to the Faculty of Health Sciences, University of the Witwatersrand in fulfillment of the requirements for the degree of Master of Medicine in the branch of Nuclear Medicine
Keywords: Melanoma; Fluorodeoxyglucose F18